Pre-Hospital Antiplatelet Therapy for STEMI Patients Undergoing Primary Percutaneous Coronary Intervention: What We Know and What Lies Ahead - Fabris, Enrico; Korjian, Serge; Coller, Barry S.; Ten Berg, Jurrien M.; Granger, Christopher B.; Gibson, C. Michael; van 't Hof, Arnoud W. J. (Thrombosis and Haemostasis, 2021)
Early recanalization of the infarct-related artery to achieve myocardial reperfusion is the primary therapeutic goal in patients with ST-elevation myocardial infarction (STEMI). To decrease the duration of ischaemia, continuous efforts have been made to improve pre-hospital treatment and to target the early period after symptom onset. In this period the platelet content of the fresh coronary thrombus is maximal and the thrombi are dynamic, and thus more susceptible to powerful antiplatelet agents. There have been substantial advances in antiplatelet therapy in the last three decades with several classes of oral and intravenous antiplatelet agents with different therapeutic targets, pharmacokinetics, and pharmacodynamic properties. New parenteral drugs achieve immediate inhibition of platelet aggregation, and fast and easy methods of administration may create the opportunity to bridge the initial gap in platelet inhibition observed with oral P2Y12 inhibitors. Moreover, potential future management of STEMI could directly involve patients in the process of care with self-administered antiplatelet agents designed to achieve rapid reperfusion. However, the potential anti-ischaemic benefits of potent antiplatelet agents will need to be balanced against their risk of increased bleeding. This study presents a comprehensive and updated review of pre-hospital antiplatelet therapy among STEMI patients undergoing primary percutaneous intervention and explores new therapies under development.
Keywords: myocardial infarction; STEMI; pre-hospital; coronary reperfusion; antiplatelet therapy; P2Y12 inhibitors; glycoprotein IIb/IIIa; selatogrel; RUC-4